2018
DOI: 10.1103/physreve.97.012910
|View full text |Cite
|
Sign up to set email alerts
|

Packing of sedimenting equiaxed dendrites

Abstract: The packing of free-floating crystal grains during solidification has a strong impact on the phase-change process as well as on the structure and the defects in the solidified material. The packing fraction is affected by the particular dendritic morphology of the grains and by their low inertia resulting from the small density difference between solid and liquid. Understanding the grain packing phenomenon during metal alloy solidification is not experimentally possible since packing is coupled to many other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In the case of the spheres, the widest grain length is simply the grain diameter. More details of the setup and grain characteristics are given in [14]. In this way, the grain-to-fluid density ratio remains close to unity with a Stokes number of St = o(10 −3 ) for both grain collections, which are conditions typically achieved in metal casting processes.…”
Section: A Setupmentioning
confidence: 84%
See 1 more Smart Citation
“…In the case of the spheres, the widest grain length is simply the grain diameter. More details of the setup and grain characteristics are given in [14]. In this way, the grain-to-fluid density ratio remains close to unity with a Stokes number of St = o(10 −3 ) for both grain collections, which are conditions typically achieved in metal casting processes.…”
Section: A Setupmentioning
confidence: 84%
“…As far as we know, the packing of nonconvex grains by sedimentation in the presence of a viscous fluid has been exclusively addressed in Ref. [14], where the packing fraction for nonconvex dendritic grains ranges from approximately 0.39 up to 0.63 depending on the grain geometry and the hydrodynamic conditions of the packing.…”
Section: Introductionmentioning
confidence: 99%
“…A more complex morphology of the solid dendrites makes them easier to form a packed structure. [31] A widely used packing condition is that is higher than . However, even if ≥ , grains cannot be made rigid when they are in the middle of a non-rigid domain, as a group of them could still sediment or float up or be dragged.…”
Section: Grain Packing Methodsmentioning
confidence: 99%
“…Very recent studies based on this method have shown that the detailed structure of the mushy zone, such as the intermetallic precipitates, influences the permeability significantly [185,186]. Another interesting study was recently made on the packing behavior of settling equiaxed dendrites [187]. A so-called packing limit (volume fraction at packing point), usually taking the value (0.637) for random close packing of equal spheres, is often used to calculate the packing equiaxed grain (characterized by the shape of grain envelope).…”
mentioning
confidence: 99%
“…On the other hand, plenty of closure laws need to be further refined. The aforementioned studies, such as on the hydrodynamic interactions between fluid and solid phases during solidification [181][182][183][184][185][186][187][188][189][190], are to be reinforced through rigorous scientific work. -Dedicated laboratory benchmark experiments for model evaluation.…”
mentioning
confidence: 99%